2017
DOI: 10.21890/ijres.328087
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Multiple Case Study about Using Game-Based Learning in STEM Classrooms

Abstract: This exploratory multiple case study attempted to examine whether game-based learning activities had any impacts on students' academic performances and behaviors, and what perceptions the teachers had toward implementing games into their classrooms. Data used in this study included 101 students' pre and post-test scores, and four structured written reflection papers by four STEM classroom teachers. The results indicated that students' academic performances improved during the week GBL was implemented. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 6 publications
0
23
0
6
Order By: Relevance
“…In addition, we used an exploratory case study approach because it enabled us to answer not only what but also how and why type questions while taking into consideration how a phenomenon was affected by the context within which it was situated (Baxter & Jack, 2008). Furthermore, data collected in this type of multiple case study design is typically a lot richer and of greater depth than found in other types of case studies or experimental designs (Vu & Feinstein, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we used an exploratory case study approach because it enabled us to answer not only what but also how and why type questions while taking into consideration how a phenomenon was affected by the context within which it was situated (Baxter & Jack, 2008). Furthermore, data collected in this type of multiple case study design is typically a lot richer and of greater depth than found in other types of case studies or experimental designs (Vu & Feinstein, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Data collected included the course instructor's written self-reflection with prompts provided by the researchers and a single unified online survey administered to the students who were enrolled in the courses taught by the instructors. Reflective practice is a research technique that helps individuals and groups reflect on their experiences and actions in order to engage in a process of continuous learning (Fook & Gardner, 2007;Vu & Feinstein, 2017). Conducting an online survey helped researchers test concepts, reflect the attitude of people, and establish the level of participant satisfaction in a large number of participants (Maxwell, 2012).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Distance education has many benefits such as ensuring the sustainability of education (Akinbadewa & Sofowora, 2020;Bruder, 1989;Omiles et al, 2019;Seage & Türegün, 2020), providing lifelong learning (Alharthi, 2020;Lou, 2004;Pambayun et al, 2019;Serhan, 2019) and reducing education costs (Al-Husban, 2020; Baggaley, 2008;Hall & Knox, 2009;Harrison & Lee, (2018) although the learner and the teacher are in different places but there are some limitations in terms of methods, schedule and time (Albalawi, 2018;Hannum, 2008;Hilton & Canciello, 2018;Thompson & McDowell, 2019;Uşun, 2006;Vu & Feinstein, 2017;Weinhandl et al, 2020). In addition, many factors such as lack of infrastructure (software, hardware etc.…”
Section: Introductionmentioning
confidence: 99%
“…Educational games or game-based learning (GBL) refers to any learning environments or activities that use games to support teaching and learning (Chang, Liang, Chou, & Lin, 2017;Vu & Feinstein, 2017). It takes advantage of game playing to engage learners with learning assignments, in which learning and winning are both important (Whitton, 2012;Woo, 2014).…”
Section: Introductionmentioning
confidence: 99%